Endocrine disrupters: the new players able to affect the epigenome - Casati, Lavinia; Sendra, Ramon; Sibilia, Valeria; Celotti, Fabio (Frontiers in Cell and Developmental Biology, 2015)
Epigenetics represents the way by which the environment is able to program the genome; there are three main levels of epigenetic control on genome: DNA methylation, post-translational histone modification and microRNA expression. The term Epigenetics has been widened by NIH to include “both heritable changes in gene activity and expression but also stable, long-term alterations in the transcriptional potential of a cell that are not necessarily heritable”. These changes might be produced mostly by the early life environment and might affect health influencing the susceptibility to develop diseases, from cancer to mental disorder, during the entire life span”. The most studied environmental influences acting on epigenome are diet, infections, wasting, child care, smoking and environmental pollutants, in particular endocrine disrupters (EDs). These are environmental xenobiotics able to interfere with the normal development of the male and female reproductive systems of wildlife, of experimental animals and possibly of humans, disrupting the normal reproductive functions. Data from literature indicate that EDs can act at different levels of epigenetic control, in some cases transgenerationally, in particular when the exposure to these compounds occurs during the prenatal and earliest period of life. Some of the best characterized EDs will be considered in this review. Among the EDs, vinclozolin (VZ) and methoxychlor (MXC) promote epigenetic transgenerational effects. Polychlorinated biphenils (PCBs), the most widespread environmental EDs, affect histone post-translational modifications in a dimorphic way, possibly as the result of an alteration of gene expression of the enzymes involved in histone modification, as the demethylase Jarid1b, an enzyme also involved in regulating the interaction of androgens with their receptor.